In situ observation of riming in mixed-phase clouds using the PHIPS probe - F. Waitz; M. Schnaiter; M. Schnaiter; T. Leisner; E. Järvinen (Atmospheric Chemistry and Physics, 2022)
Mixed-phase clouds consist of both supercooled liquid water droplets and solid ice crystals. Despite having a significant impact on earth's climate, mixed-phase clouds are poorly understood and not well represented in climate prediction models. One piece of the puzzle is understanding and parameterizing riming of mixed-phase cloud ice crystals, which is one of the main growth mechanisms of ice crystals via the accretion of small, supercooled droplets. Especially the extent of riming on ice crystals smaller than 500 µm is often overlooked in studies – mainly because observations are scarce. Here, we investigated riming in mixed-phase clouds during three airborne campaigns in the Arctic, the Southern Ocean and US east coast. Riming was observed from stereo-microscopic cloud particle images recorded with the Particle Habit Imaging and Polar Scattering (PHIPS) probe. We show that riming is most prevalent at temperatures around −7 ∘C, where, on average, 43 % of the investigated particles in a size range of 100≤D≤700<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="72pt" height="11pt" class="svg-formula" dspmath="mathimg" md5hash="d88fb6175856f7111ba0e98719016573"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-22-7087-2022-ie00001.svg" width="72pt" height="11pt" src="acp-22-7087-2022-ie00001.png"/></svg:svg> µm showed evidence of riming. We discuss the occurrence and properties of rimed ice particles and show the correlation of the occurrence and the amount of riming with ambient microphysical parameters. We show that riming fraction increases with ice particle size (<20 % for D≤200 µm, 35 %–40 % for D≥400 µm) and liquid water content (25 % for LWC ≤0.05 g m−3, up to 60 % for LWC = 0.5 g m−3). We investigate the aging of rimed particles and the difference between “normal” and “epitaxial” riming based on a case study.